2016
DOI: 10.4238/gmr.15027885
|View full text |Cite
|
Sign up to set email alerts
|

Effects of siRNA-mediated silencing of Sal-like 4 expression on proliferation and apoptosis of prostate cancer C4-2 cells

Abstract: ABSTRACT. The aim of this study was to evaluate the effects of small interfering RNA (siRNA)-inhibited expression of the Sal-like 4 (SALL4) gene on the proliferation, colony formation, and apoptosis of prostate cancer C4-2 cells. C4-2 cells were cultured and divided into a si-SALL4 group, a negative control siRNA group, and a blank control group. SALL4 mRNA levels and protein expression were detected by real-time polymerase chain reaction and western blot, respectively. Changes in the cell proliferation and co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…Overexpression of antiapoptotic Bcl-2 inhibits cell apoptosis and leads to an imbalance between enhanced proliferation and weakened programmed death through downregulation of Bax [73,74]. SALL4 overexpression in MDS and AML cells results in an increase in Bcl-2 expression and cell survival [75], whereas SALL4 knockdown markedly inhibits Bcl-2 expression in prostate cancer [76], breast cancer [16,77], colorectal cancer (CRC) [78], and nasopharyngeal carcinoma (NPC) [79], and it induces the expression of pro-apoptotic Bax in prostate cancer [76] and NPC [79].…”
Section: Sall4 Regulates Expression Of Bcl-2 and Baxmentioning
confidence: 99%
“…Overexpression of antiapoptotic Bcl-2 inhibits cell apoptosis and leads to an imbalance between enhanced proliferation and weakened programmed death through downregulation of Bax [73,74]. SALL4 overexpression in MDS and AML cells results in an increase in Bcl-2 expression and cell survival [75], whereas SALL4 knockdown markedly inhibits Bcl-2 expression in prostate cancer [76], breast cancer [16,77], colorectal cancer (CRC) [78], and nasopharyngeal carcinoma (NPC) [79], and it induces the expression of pro-apoptotic Bax in prostate cancer [76] and NPC [79].…”
Section: Sall4 Regulates Expression Of Bcl-2 and Baxmentioning
confidence: 99%
“…53 Recently, SALL4 has been demonstrated to be significantly upregulated in certain types of human cancer, including hepatocellular carcinoma, 54 intrahepatic cholangiocarcinomas, 55 esophageal squamous cell carcinoma, 54 breast cancer, 39 gastric cancer, 56 lung cancer, 30 and prostate cancer. 57 Deng et al 55 revealed that an upregulation of SALL4 expression could help to the cancer progression in intrahepatic cholangiocarcinoma as well as associated with poor prognosis in the cholangiocarcinoma patients. 54 In another study, Oikawa et al 58 indicated that upregulation of SALL4 expression was associated with an increase of cell proliferation of hepatocellular carcinoma cells.…”
Section: Discussionmentioning
confidence: 99%
“…Another example is Sal-like 4 (SALL4), an oncogene factor with stimulatory impacts on the proliferation and metastasis of cancer cells [ 107 , 108 ]. Decreasing the expression of SALL4 using siRNA stimulates apoptotic cell death in PCa cells via upward regulation of pro-apoptotic factor Bax and downward regulation of anti-apoptotic factor Bcl-2 [ 109 ].…”
Section: Sirna Targets Signaling Pathways: Focus On Pca Therapymentioning
confidence: 99%